2023
DOI: 10.1038/s41467-023-42296-1
|View full text |Cite
|
Sign up to set email alerts
|

Resonant cavity phosphor

Tae-Yun Lee,
Yeonsang Park,
Heonsu Jeon

Abstract: While phosphors play an immensely important role in solid-state lighting and full-colour displays, it has been noted lately that their performance can be largely improved via structural engineering. Here, phosphor material is synergistically merged with yet another structurally engineered platform, resonant cavity (RC). When a 40-nm-thick colloidal quantum dot (CQD) film is embedded in a tailored RC with a moderate cavity quality factor (Q ≈ 90), it gains the ability to absorb the majority (~87%) of excitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…1a, b; Supplementary Fig. S7), similar to the recently published Cx36 structure 4 . The N-terminal gating helix (NTH) is unresolved in our reconstructions (Supplementary Fig.…”
Section: Dear Editorsupporting
confidence: 86%
See 2 more Smart Citations
“…1a, b; Supplementary Fig. S7), similar to the recently published Cx36 structure 4 . The N-terminal gating helix (NTH) is unresolved in our reconstructions (Supplementary Fig.…”
Section: Dear Editorsupporting
confidence: 86%
“…The development of selective inhibitors of Cx36 could be of therapeutic value. Although a structure of Cx36 has been determined recently 4 , it remains unclear how drugs inhibit the Cx36 and other Cx channels.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the development of deep-blue TADF-OLEDs with high efficiency and good color purity still lags far behind. 8–11 The reason is that in order to achieve efficient and narrow-band deep-blue emission, the D and A building units need to meet the prerequisites: (1) both relatively weak D and A moieties with less electron-donating and electron-withdrawing abilities are required to form a relatively weak D–A interaction and thereby reduced intramolecular charge transfer (CT) effects, ensuring a sufficiently wide bandgap ( E 1 CT > 3.0 eV); (2) the local excited (LE) triplet state energy levels of D ( 3 LE D ) and A ( 3 LE A ) should be close to that of the 1 CT state of D–A molecules. As a result, the generated effective vibronic coupling (VC) and SOC interactions between 3 LE D/A , 3 CT and 1 CT states of emitters can facilitate the efficient RISC process; 12 (3) the D and A units should possess high structural rigidity to ensure high photoluminescence quantum efficiency (PLQY) and narrow-band emitting spectra.…”
mentioning
confidence: 99%
“…Furthermore, Bae et al reported that AIGS/AgGaS 2 core–shell NCs, synthesized via the hot injection method, exhibit near-unity PLQY with a narrower FWHM of 30 nm in the visible range (460–620 nm). 23 However, improving the PLQY through trial and error has been prioritized over understanding the optical emission spectra.…”
mentioning
confidence: 99%